Dandelion [videorecording (Blu-Ray)] - Riegel, Nicole; Doherty, Thomas (Actor); Layne, KiKi; Nicholls-King, Melanie (IFC Films, 2025)
A struggling singer-songwriter falls into an intoxicating romance that leads her to a deeper appreciation of her artistic journey and the discovery of a voice that is authentically her own.